Performance Analysis of Vertical Sectorization in LTE Network Using AAS - Fengyi Yang; Jianmin Zhang; Weiliang Xie; Xuetian Zhu (Dianxin kexue)
An evaluation of vertical sectorization in LTE field trial was conducted. The field trial results show that the performance of vertical sectorization will be decreased due to the co-frequency interference between the inner and outer cells. Furthermore, some practical suggestions on the deployment of vertical sectorization in LTE network were proposed.